Prospects for the development of functional expansion of individual low-cost prosthetic limbs for people with disabilities with intelligent sensors. Issue 1 (January 2021) - Gryaznov, D; Zhmud, V; Avrmachuk, V; Malakhov, D; Nosek, J; Dimitrov, L
Abstract: Despite the development of medicine, as well as robotics aimed at helping people with disabilities, most disabled people with missing limbs cannot hope for a full life with the help of bionic prostheses, since these products are made strictly individually, and their control requires expensive surgeries to implant sensors. In addition, such prostheses themselves are very expensive. An alternative solution is to reduce the cost of such prostheses as much as possible and abandon the implantable sensors of signals of the human nervous system. The paper proposes a method for solving such a problem using a variety of sensors that remove signals from the skin surface without invasive surgery.